IDENTIFIKASI LOGAM BERAT Hg, Pb DAN Cd DI ALIRAN SUNGAI BATANG KUANTAN, KABUPATEN KUANTAN SINGINGI - Asregi Asril; Rosa Murwindra; Jumriana Rahayu Ningsih (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
The identification of heavy metals Hg, Pb and Cd in the Batang Kuantan River, Kuantan Singingi Regency has been carried out successfully. Heavy metals are measured not only from their heavy metal content such as Hg, Pb and Cd but also from the pH level of the river flow itself. The research location is at the Batang Kuantan River, which is measured from 3 points. Changes in Data Observed / Measured are the quality levels of heavy metals in the waters. The research model used includes field research using survey and laboratory methods. The research design was analyzed using the Atomic Absorption Spectometer (AAS). The water sample was given HNO3 until it was acidic and filtered so that there was no sedimentation, then analyzed by AAS. Heavy metal analysis result data technique is compared with quality standard of government regulation no 82 of 2001 regarding water pollution control and water quality management. Pb did not have a problem because the levels were not found. Whereas for Cu and Cd in the category of concentration threshold for reasonableness, which ranged from 0.158-0.1598 ppm and 0.0233-0.2769 ppm.